Edukasi Kesehatan Reproduksi Remaja bagi Siswa SMP Ma’arif Borobudur - Rohmayanti Rohmayanti; Rahayu Gustiana; Alda Setyowati; Fitri Dewi Kinasih; Safira Nafi`ah; Fikri Dwi Andriyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Reproductive health is a topic that needs to be known in adolescents because there is a critical period that is both normative and maladaptive in adolescent development. Junior high school (SMP) students are categorized as early adolescents (12–15 years old). Their characteristics include unstable behaviour, tending to be emotional and unrealistic, and being a critical period for various information so that they can experience problems such as promiscuity, teenage pregnancy, abortion, sexually transmitted diseases (STDs), and others. Grade 7 students at SMP Ma'arif Borobudur have not yet received information about reproductive health. The method used was providing reproductive health education using multimedia and group discussions. The sub-topics of this health counselling consisted of material on introducing reproductive organs, sexually transmitted diseases, unwanted pregnancy, premarital sex, and healthy reproductive tips. The activity was carried out in four stages: problem assessment, socialization of plans, education, and evaluation. The activity improved knowledge among adolescents about reproductive health, seen in pretest results with a mean of 81.08 and posttest scores of 86.70 in the range of 0-100. It shows that reproductive health education can improve adolescents' knowledge, so this activity needs to be carried out periodically.